2022
DOI: 10.3390/jpm12030456
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of SNPs at miRNA Binding Sites as Biomarkers of Gastric and Colorectal Cancers: A Systematic Review

Abstract: Dysregulated mRNA–miRNA profiles might have the prospective to be used for early diagnosis of gastrointestinal cancers, estimating survival, and predicting response to treatment. Here, a novel biomarker based on miRNAs binding to mRNAs in single nucleotide polymorphism (SNP) sites related to gastrointestinal cancers is introduced that could act as an early diagnosis. The electronic databases used for the recruiting published articles included EMBASE, SCOPUS, Web of Science, and PubMed, based on MESH keywords a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The data analysis of previous and recent systematic reviews revealed how there is the possibility that miR-196a and miR-196b may represent a potential prognostic biomarker [ 47 ] in addition to their diagnostic potential. In fact, Cheng et al (2021), in an bioinformatics data analysis of two databases (TCGA-HNSC dataset and GSE31277 dataset), identified for miR-196b an area under the curve (AUC) of 0.767 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data analysis of previous and recent systematic reviews revealed how there is the possibility that miR-196a and miR-196b may represent a potential prognostic biomarker [ 47 ] in addition to their diagnostic potential. In fact, Cheng et al (2021), in an bioinformatics data analysis of two databases (TCGA-HNSC dataset and GSE31277 dataset), identified for miR-196b an area under the curve (AUC) of 0.767 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whenever a potential cancer-suppression mechanism is discovered in a species, there is the real possibility of identifying a new molecular target or therapeutic approach. Therefore, the investigation of genomic alterations, such as CNVs, can direct clinical research towards the discovery of new toolkits able to guide scientists towards the exploration of more focused research topics, such as, for example, specific microRNAs or their targets [ 96 , 97 ].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…73,74 MicroRNAs (miRNAs), one type of short non-coding RNA consisting of around 20-25 nucleotides, have a role in the biological processes by modifying the post-translational events of mRNAs. 75 MiRNAs regulate gene expression through binding to specific seed sequences in the 3 0 untranslated region (3 0 UTR) of target genes. 75 Moreover, miRNAs are considered significant biomolecules involved in the beginning, development, prognosis, diagnosis, and therapy of different pathophysiological indications due to their role as fine tuners of gene expression, control of signaling, and molecular-cellular processes.…”
Section: Non-coding Rnas and Oxidative Stress In The Management Of Ty...mentioning
confidence: 99%
“…75 MiRNAs regulate gene expression through binding to specific seed sequences in the 3 0 untranslated region (3 0 UTR) of target genes. 75 Moreover, miRNAs are considered significant biomolecules involved in the beginning, development, prognosis, diagnosis, and therapy of different pathophysiological indications due to their role as fine tuners of gene expression, control of signaling, and molecular-cellular processes. 8,75 Typically a nucleotide sequence of over 200 bp displaying as long noncoding RNAs (lncRNAs) influences gene expression by many mechanisms.…”
Section: Non-coding Rnas and Oxidative Stress In The Management Of Ty...mentioning
confidence: 99%
See 1 more Smart Citation